Cyberbullying on Social Media and Its Implications for the Mental Health of Generation Z in the Context of the Second Principle - Hardiyanto, Lutfi; Iriansyah, Herinto Sidik; Pudjiastuti, Sri Rahayu (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
Cyberbullying, an escalating issue, involves humiliating and threatening others electronically, primarily on platforms like Instagram. Generation Z, familiar with technology from childhood, faces the highest cyberbullying rates. This study aims to describe the phenomenon of cyberbullying on social media against the mental health of Generation Z in Jakarta about the view of the second principle of Pancasila. This study uses the literature review theory with data obtained in the form of articles, books, journals, documents, and websites that have been carefully studied to trigger the social phenomenon that is being pursued in society from 2017 to 2023 obtained from the electronic database Google Scholar. The results of this study show that cyberbullying on Generation Z on social media has a huge impact that affects mental health in the context of civilized humanity, which is considered a violation of the second principle of Pancasila which highly upholds the value of justice because the rights and dignity of a person are not respected, where an individual is treated unequally because another individual considers himself to be better in a certain aspect. The individual acts arbitrarily and there is no behavior of mutual love among fellow human beings.